Circulating follicular helper T cells and subsets are associated with immune response to hepatitis B vaccination - Mingjuan Yin; Yongzhen Xiong; Lingfeng Huang; Gang Liu; Zuwei Yu; Yi Zhao; Jie Zhao; Yan Zhang; Tingyu Lian; Jingxiao Huang; DongMei Liang; JinMei Zeng; et al. (Taylor & Francis Group, 2021)
Around 5-10% of healthy vaccinees lack or produce an inadequate antibody response following receipt of a standard hepatitis B vaccination regimen. Studying immune response to hepatitis B vaccination could promote researches of immunological events contributing to this poor response. To address this, we investigated follicular helper T (Tfh) cells and firstly demonstrated similar kinetics between circulating Tfh (cTfh) cells and Tfh cells derived from mice spleen after hepatitis B vaccination. And cTfh cells were positively associated with anti-HBs at one week after vaccination (D7). Furthermore, we found PBMCs stimulated by HBsAg showed preferential activation of CXCR3− Tfh cells subsets in vitro. The expression of transcription factor BCL6 in CD4+ T cell significantly differed between D7 and four weeks after vaccination (D28). However, dynamic curve of CD19+ B cells tended to rise then fall but no significant trends were observed. Our findings revealed a decrease in cTfh cells and subset skewing contribute to reduced antibody responses in immune response to hepatitis B vaccination, which indicated the importance of Tfh cell in facilitating the optimization of vaccine efficacy.